Deep Pectoral Myopathy (DPM) in broiler chickens - GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ), I.; BOUGIOUKLIS (Π. ΜΠΟΥΠΟΥΚΛΗΣ), P.; IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ), P.; LEKKAS (Σ. ΛΕΚΚΑΣ), S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Macroscopic lesions were observed in pectoralis supracoracoides in carcases of broilers 7-8 weeks-old from various regions of Greece. The broilers were descendants from breeders of different genealogie lines, their feeding was regular and their growth rate was very good. An important information in the history of all involved broiler flocks was that lesions were observed in the chickens which were led to slaughteries from 3 to 10 days after house's decongestion. Macroscopic lesions were found mainly in the middleportion of the muscles and were either petechial hemorrhages or focal necrosis from greenish to red-brownish coloration. The bacteriological examination was negative, while the histological examination showed ischaemic necrosis of the muscle fibres. As the supracoracoid muscle is responsible for wing movements, trigger ofthese lesions might be the voluntary severe wing movements. It issuggested that sufficient prevention of deep pectoral myopathy (DPM) in broiler flocks may be achieved, when careful handling is used for their selection and mainly by the shortly removal of the remaining chickens into the houses after their decongestion.